Neonatally Diagnosed Imperforate Hymen: Hymen Saving Surgery - Maram A. Enani,; Wejdan O. Ba-Amer,; Alfaf S. Aljohani,; Shahad A. Aljohani,; Noor A. Aljohani,; Yousef M. Qazli,; Ettedal A. Aljahdali, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Imperforate hymen is the most common obstructive anomalies of the female genital tract. It is usually an isolated anomaly but can be rarely syndromic. It can be asymptomatic until puberty, but the diagnosis as early as neonatal period has been reported and as with our neonate with hematocolpos. The aim of this case report is to present the early diagnosis and treatment of a female neonate with imperforate hymen taking into consideration the religious and traditional value of preservation of virginity in our community, and to stress the importance of careful post birth examination of the neonate and early management to avoid complications of late diagnosis.